2019
DOI: 10.1016/j.acha.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven spectral decomposition and forecasting of ergodic dynamical systems

Abstract: We develop a framework for dimension reduction, mode decomposition, and nonparametric forecasting of data generated by ergodic dynamical systems. This framework is based on a representation of the Koopman and Perron-Frobenius groups of unitary operators in a smooth orthonormal basis of the L 2 space of the dynamical system, acquired from time-ordered data through the diffusion maps algorithm. Using this representation, we compute Koopman eigenfunctions through a regularized advection-diffusion operator, and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
274
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 145 publications
(278 citation statements)
references
References 88 publications
(318 reference statements)
4
274
0
Order By: Relevance
“…This behavior indicates that including previous states by delay-coordinate mapping plays a significant role in the performance of the method at long leads, which challenge many traditional approaches. This is consistent with previous work, which has shown that incorporating delays increases the capability of kernel algorithms to extract dynamically intrinsic coherent patterns in the spectrum of the Koopman operator 15,16 , including ENSO and its linkages with seasonal and decadal variability of the climate system [24][25][26] . Given our main focus here on the extended-range regime, Figure 1 Another important consideration in ENSO prediction is the seasonal dependence of skill, exhibiting the so-called "spring barrier" 6 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This behavior indicates that including previous states by delay-coordinate mapping plays a significant role in the performance of the method at long leads, which challenge many traditional approaches. This is consistent with previous work, which has shown that incorporating delays increases the capability of kernel algorithms to extract dynamically intrinsic coherent patterns in the spectrum of the Koopman operator 15,16 , including ENSO and its linkages with seasonal and decadal variability of the climate system [24][25][26] . Given our main focus here on the extended-range regime, Figure 1 Another important consideration in ENSO prediction is the seasonal dependence of skill, exhibiting the so-called "spring barrier" 6 .…”
Section: Resultssupporting
confidence: 92%
“…The KAF approach employed in this work utilizes nonlinear-kernel algorithms to enhance the information content of the predictor vectors to beyond linear functions of the input data, and leverages that information through the use of statistical learning theory 10 and operator-theoretic ergodic theory 11,12 to optimally capture the evolution of a response variable (here, an ENSO index) under partially observed nonlinear dynamics. Here, we build KAF models using the class of kernels introduced in the context of nonlinear Laplacian spectral analysis (NLSA) 13,14 algorithms, which provably capture modes of high temporal coherence 15,16 , evolving at intrinsic timescales in the spectrum of the Koopman evolution operator 17 of the underlying dynamical system. This capability is realized without ad hoc prefiltering of the input data through the use of delay-coordinate maps 18 and a nonlinear (normalized Gaussian) kernel function 19 , measuring similarity between delay-embedded sequences.…”
mentioning
confidence: 99%
“…Moreover, in the SIC field, these modes exhibit appreciable wavenumber-2 variability in the meridional direction (Figure 3a), consistent with the seasonal growth and melting of Antarctic sea ice in response to the seasonal cycle. Analogous relationships between annual-cycle modulated patterns and sea-ice reemergence phenomena (Blanchard-Wrigglesworth et al, 2011;Holland et al, 2013) have also been identified in the Arctic (Bushuk et al, 2014;2015;2017), but have not received similar attention in the Southern Ocean.…”
Section: Wavenumber-2 Acw Modesmentioning
confidence: 99%
“…Issues pertaining to non-compactness or continuous spectra of Koopman operators associated with systems of high complexity are beyond the scope of this paper. Although such cases can theoretically be handled, the numerical analysis is often challenging and typically requires regularization, which is, for instance, implicitly given by Galerkin projections [25]. This is discussed in detail in the aforecited work by Giannakis.…”
Section: Galerkin Approximationmentioning
confidence: 99%